Pengaruh Leverage, Proporsi Komisaris Independen, dan Auditor Switching Terhadap Tax Avoidance (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021) - Palupi, Anindita; Afifudin, Afifudin; Nandiroh, Umi (Universitas Islam Malang, 2023)
This study aims to examine the results of leverage, the proportion of independent commissioners and auditor switching on tax avoidance in mining companies listed on the Indonesia Stock Exchange in 2017-2021. In this study using fraud triangle theory, where this theory states that there are three components that generally cause fraud, namely pressure proxied by leverage, opportunity proxied by the proportion of independent commissioners and rationalization proxied by auditor switching. This study uses secondary data from the financial statements and annual reports of the Indonesia Stock Exchange. The type of data used in this study is quantitative. This study uses purposive sampling method in sampling and multiple linear regression analysis in data analysis method with the help of statistical computer software SPSS version 14. The results showed that simultaneously leverage, proportion of independent commissioners, and auditor switching have a significant positive effect on tax avoidance. Partially, leverage has a significant positive effect on tax avoidance, the proportion of independent commissioners has a significant negative effect on tax avoidance, auditor switching has no effect on tax avoidance. The results of this study reveal that the variables used in this study are only able to contribute 11.1% to tax avoidance, while the remaining 88.9% is influenced by other variables outside this study.Keywords : Leverage, the proportion of independent commissioners, auditor switching, tax avoidance